Aplikasi Sistem Informasi Geografi (Gis) untuk Pemetaan dan Simulasi Erosi Tanah - Mujiyo Mujiyo; Sumani Sumani; Joko Winarno (Universitas Sebelas Maret, 2007)
The aims of the research are to use the technology of the geographic information system for mapping and simulation of the soil erosion, and to know the difference betweet actual and potential erosion on the spesific land use type. The area of the research is Jumapolo District, Karanganyar Regency. USLE equation method (R=R.K.L.S.C.P) was used to predict the soil erosion intensity. The steps of the research are (1) pre-survey, prepared equipments for suvey, (2) survey, was done by exploring predertemined land map unit, and (3) labs, analysis of the soil samples, the rainfall data and teh ArcView GIS. Analysis was done using rating based on Zachar (1982) in order to know the difference of the soil erosion intensity.The results of the research are first, geographic information system is useful to mapping and simulation of the soil erosion, especially to calculate data that numerous and difficult, to overlay, to layout the map (or the other spasial data) and the statistic of land area, second, Jumapolo District has variability of the soil erosion intensity i.e. very slight 25,77 ha (0,62% of the agriculture land area), slight 815,71 ha (20,39%), moderate 1.094,69 ha (25,49%), severe 1.150,58 ha (33,09%), very severe 827,25 ha (18,88%) and catastrophic 243,69 ha (1,53%) and third, the change of the land unit type and the conservation technic can change the soil erosio intensity. Simulation process result that land area which have soil erosion intensity severe, very severe and catastrophic changes become slight and moderate, therefore the new compotitions of the soil erosion intensity are very slight 25,77 ha (0,62%), slight 1.665,48 ha (40,06%), moderate 2.466,43 ha (59,32%), and each severe, very severe and catastrophic 0 ha (0%).